1997
DOI: 10.1038/sj.onc.1200810
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activation of the αPDGFR defines a domain that negatively regulates receptor dimerization

Abstract: The a platelet derived growth factor receptor (aPDGFR) extracellular Immunoglobulin (Ig) like domains 1 ± 3 contain major determinants for ligand interaction. We now report that a deletion of Ig-like loop 3, but not Iglike loop 1 or 2, of the aPDGFR causes ligandindependent transformation in NIH3T3 cells. Biochemical analyses of aPDGFR mutants lacking Ig-like loop 3 indicate that cellular transformation is mediated by ligand-independent activation of the aPDGFR tyrosine kinase activity as determined by recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The second Ig-like domain appears to be more critical in preventing spontaneous receptor dimerization, and this correlates with the more important role played by this domain in NGF binding (24,33,34,36). In platelet-derived growth factor receptors, Ig-like domains 1 to 3 participate in ligand binding; however, only deletion of the Ig-like domain 3 caused oncogenic activation (32). Chimeric receptors between TrkA and c-Kit demonstrated that dimerization could also be achieved by retaining the Iglike structure but exchanging the TrkA Ig-like domains for a c-Kit domain responsible for dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…The second Ig-like domain appears to be more critical in preventing spontaneous receptor dimerization, and this correlates with the more important role played by this domain in NGF binding (24,33,34,36). In platelet-derived growth factor receptors, Ig-like domains 1 to 3 participate in ligand binding; however, only deletion of the Ig-like domain 3 caused oncogenic activation (32). Chimeric receptors between TrkA and c-Kit demonstrated that dimerization could also be achieved by retaining the Iglike structure but exchanging the TrkA Ig-like domains for a c-Kit domain responsible for dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…A mutant PDGFA receptor lacking Ig-like domain 3 results in growth factor-independent receptor dimerization and activation (55), and an Ig-like domain contained within the extracellular domain of the TrkA receptor serves a similar function (56). Interestingly, the structural features of the PDGF receptor A and TrkA receptors that participate in these effects are contained within the receptor's ligand binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…7D) unequivocally demonstrates that the efficient homodimerization of the truncated RPTP␣ can occur in a ligand-independent fashion. However, since some truncated receptor PTKs lacking all or part of the ECD undergo ligand-independent dimerization, whereas the full-length receptors do not (15,22,57), the fact that the RPTP␣ ECD deletion mutant dimerized does not necessarily imply that the dimerization of full-length RPTP␣ is also ligand independent. So far, we have been unable to cross-link endogenous RPTP␣ in embryonic fibroblasts or retrovirally transduced RPTP␣ in RPTP␣ Ϫ/Ϫ embryonic fibroblasts derived from RPTP␣ Ϫ/Ϫ mice (50).…”
Section: Discussionmentioning
confidence: 99%